Ketamine decreases sensitivity of male rats to misleading negative feedback in a probabilistic reversal-learning task - Rychlik, Michal; Bollen, Eva; Rygula, Rafal (Psychopharmacology, 2017)
Rationale Depression is characterized by an excessive attribution of value to negative feedback. This imbalance in feedback sensitivity can be measured using the probabilistic reversal-learning (PRL) task. This task was initially designed for clinical research, but introduction of its rodent version provides a new and much needed translational paradigm to evaluate potential novel antidepressants. Objectives In the present study, we aimed at evaluating the effects of a compound showing clear antidepressant properties—ketamine (KET)—on the sensitivity of rats to positive and negative feedback in the PRL paradigm. Methods We trained healthy rats in an operant version of the PRL task. For successful completion of the task, subjects had to learn to ignore infrequent and misleading feedback, arising from the probabilistic (80:20) nature of the discrimination. Subsequently, we evaluated the effect of KET (5, 10, and 20 mg/kg) on feedback sensitivity 1, 24, and 48 h after administration. Results We report that acute administration of the highest dose of KET (20 mg/kg) rapidly and persistently decreases the proportion of lose–shift responses made by rats after receiving negative feedback. Conclusion Present results suggest that KET decreases negative feedback sensitivity and that changes in this basic neurocognitive function might be one of the factors responsible for its antidepressant action.